The Global Village Revisited: Art, Politics, and Television Talk Shows - Dixon, Kathleen (Lexington Books, 2009)
Cultural studies scholarship on the television talk show, especially the 'audience discussion' genre, was guardedly hopeful about its democratic or feminist potential. In this exciting new volume, Kathleen Dixon investigates the relationship between the talk genre and democracy, but through a new emphasis on art, broadly defined. The Global Village Revisited: Art, Politics, and Television Talk Shows explores three case studies from Belgium, Bulgaria, and the United States, and reveals how these cases interanimate to produces a new view of the talk show as a global phenomenon, and as a negotiation among the forces of late capitalism, the unnamed but still palpable audience, and the individual rhetors, artists, and technicians who make the shows. Dixon treats the globalization of media and culture as a dynamic process that yields different results according to time and place. While the way in which television talk shows serve democracy may be hard to define precisely, The Global Village Revisited demonstrates the importance and necessity of this question in cultural studies.